Analysis of drug purchases aft er the entry into force of the federal contract system - M. G. Malaev (Izdatelstvo OKI, 2018)
According to the authors of the Federal Law of 05.04.2013 №44 -FZ «On the contract system in the procurement of goods, works and services for state and municipal needs» new rules of organization and control in procurement should be accompanied by a reduction of waste and the risk of corruption schemes by increasing the «transparency» of the bidding procedure. Performed work showed that before the implementation of the law imposed on hopes still far away, in any case, in terms of drug procurement.